Probabilistic assessment and sensitivity analysis of existing concrete bridge via surrogate modeling - Lukáš Novák; Drahomír Novák (Acta Polytechnica CTU Proceedings, 2022)
The paper is focused on probabilistic assessment and sensitivity analysis of existing prestressed concrete bridge using surrogate model in form of Polynomial Chaos Expansion (PCE). The bridge was selected in the framework of the European Project INTERREG AUSTRIA-CZECH REPUBLIC "TCZ190 SAFEBRIDGE" focused on advanced numerical analysis of existing bridges represented by non-linear finite element model. In this study, surrogate model in form of PCE was created, which represents very efficient type of surrogate model. One of significant advantages of PCE is powerful post-processing including sensitivity and moment analysis of the response, which is important part of probabilistic analysis. The obtained numerical results of advanced stochastic analysis consisting of uncertainty quantification and sensitivity analysis of the existing bridge structure are presented in the paper.